Social Support and Psychological Well‑being Among Islamic Private Junior High School Students - Umi Anugerah Izzati; Nur Hidayah; Hendra Hidayat; Fifi Khoirul Fitriyah; Wiryo Nuryono; Evi Winingsih; Wan Ab Aziz Wan Daud (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Junior high school students are in a developmental phase that is vulnerable to various psychological problems, thus requiring appropriate support to maintain their psychological well-being. One strategy for identifying these problems is the Problem Checklist (DCM). Social support is an important factor influencing students’ psychological well-being. This study aims to determine the relationship between social support and psychological well-being in private Islamic junior high school students in Surabaya. This study used a quantitative approach with a sample of 565 students selected from one of the private Islamic junior high schools in Surabaya. The data analysis technique used was product-moment correlation, performed in SPSS. The study found a significant positive relationship between social support and students’ psychological well-being, with a correlation coefficient of 0.585 and a p-value of 0.000. This finding indicates that the greater the social support students receive from parents, peers, and teachers, the higher their psychological well-being. The implications of this study emphasize the role of schools in strengthening social support through character development programs, collaborative activities, and structured mentoring to maintain and improve students’ psychological well-being.